TUJUAN ADMINISTRASI PENDIDIKAN DAN FUNGSI ADMINISTRASI PENDIDIKAN - Takdirmin; Suci Valina Maharani; Sri Awaliyah; Uswatul Fatihah; Suliasti Cahayadi (STKIP Subang, 2026)
Educational administration plays a crucial role in supporting the implementation of education in elementary schools. Educational administration is not only concerned with record-keeping but also encompasses the management of all school activities to ensure they run smoothly and in accordance with educational objectives. This paper aims to discuss the objectives of educational administration and the functions of educational administration in the context of elementary school education. The method used is a literature review by reviewing various books and journals relevant to the topic of educational administration. The results of the study indicate that the purpose of educational administration is to help achieve educational objectives through effective management of school resources. The functions of educational administration, which include planning, organizing, implementing, and supervising, are essential in the implementation of school activities. The implementation of good educational administration can support the smooth running of the learning process and create an orderly learning environment in elementary schools